CREATIVE SKILLS AND CAPABILITIES OF TEACHERS TEACHING ADULT CLASS - Dilrabo AKHMEDOVA (Scholar Express Journal, 2023)
In order to meet the new socio-cultural order, the modern teacher must be ready for innovative activities. At the same time, according to experts, the organization of training subjects of innovative educational activities should have its own characteristics depending on the level of fundamental changes. The main rules of training senior teachers for the introduction of educational innovations will be effective if they are based on a targeted approach and aimed at mastering the methods of developing and implementing an innovative development program of an educational institution
Keywords: logical thinking; development; heuristic ability; methodology